Oral Microbiota Composition and Function Changes During Chronic Erythematous Candidiasis - Lyu, Xin; Zheng, Hui; Wang, Xu; Zhang, Heyu; Gao, Lu; Xun, Zhe; Zhang, Qian; He, Xuesong; Hua, Hong; Yan, Zhimin; Chen, Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Oral microbiota is constantly changing with the host state, whereas the oral microbiome of chronic erythematous candidiasis remains poorly understood. The aim of this study was to compare oral microbial signatures and functional profiling between chronic erythematous candidiasis and healthy subjects. Using shotgun metagenomic sequencing, we analyzed the microbiome in 12 chronic erythematous candidiasis, 12 healthy subjects, and 2 chronic erythematous candidiasis cured by antifungal therapy. We found that the salivary microbiota of chronic erythematous candidiasis was significantly different from that of healthy subjects. Among them, Rothia mucilaginosa and Streptococcus mitis were the most abundant disease-enriched species (Mann-Whitney U-test, P < 0.05). In addition, co-occurrence network analysis showed that C. albicans formed densely connected modules with oral bacterial species and was mainly positive connected to Streptococcus species. Furthermore, we investigated the functional potentials of the microbiome and identified a set of microbial marker genes associated with chronic erythematous candidiasis. Some of these genes enriching in chronic erythematous candidiasis are involved in eukaryotic ribosome, putative glutamine transport system, and cytochrome bc1 complex respiratory unit. Altogether, this study revealed the changes of oral microbial composition, the co-occurrence between C. albicans and oral bacteria, as well as the changes of microbial marker genes during chronic erythematous candidiasis, which provides evidence of oral microbiome as a target for the treatment and prevention of chronic erythematous candidiasis.